Treatment of Localized Gingival Recession by Means Tunnel Technique after the Orthodontic Treatment. A Follow-Up of 1 Year - Marcelo Imano; Paula Porto Spada; Juliana Marchioro Souza Macalossi; Tatiana Miranda Deliberador (Case Reports in Dentistry)
Facial and dental esthetics are the objectives of dental treatment, and, for this, it is necessary that specialties such as periodontics and orthodontics work together. The objective of this article is to report a clinical case with the solution of localized gingival recession after orthodontic treatment, using tunneled subepithelial connective tissue grafts with follow-up for 1 year. The patient underwent orthodontic treatment for 1 year. Prior to the start of treatment, a gingival recession of 5 mm was already present on tooth 31. One month after the completion of treatment, the patient was subjected to a tunneled subepithelial connective tissue graft, with the purpose of covering the exposed root. We observed the effectiveness of the procedure and patient satisfaction with the results obtained. The subepithelial connective tissue graft was successful in this case, and the collaboration of specialists is important to provide the best treatment for the patient.